NOD2 (CARD15) mutations in Crohn's disease are associated with diminished mucosal α-defensin expression. Issue 11 (11th October 2004) - Wehkamp, J; Harder, J; Weichenthal, M; Schwab, M; Schäffeler, E; Schlee, M; Herrlinger, K R; Stallmach, A; Noack, F; Fritz, P; Schröder, J M; Bevins, C L; et al.
Abstract : Background: Mutations in NOD2, a putative intracellular receptor for bacterial peptidoglycans, are associated with a subset of Crohn's disease but the molecular mechanism linking this protein with the disease pathogenesis remains unclear. Human α defensins (HD-5 and HD-6) are antibiotic effector molecules predominantly expressed in Paneth cells of the ileum. Paneth cells also express NOD2. To address the hypothesis that the function of NOD2 may affect expression of Paneth cell defensins, we compared their expression levels with respect to NOD2 mutations in Crohn's disease. Methods: Forty five Crohn's disease patients (24 with NOD2 mutations, 21 with wild-type NOD2) and 12 controls were studied. Real time reverse transcription-polymerase chain reaction was performed with mucosal mRNA for HD-5, HD-6, lysozyme, secretory phospholipase A2 (sPLA2 ), tumour necrosis factor α, interleukin 8, and human hypoxanthine phosphoribosyltransferase (housekeeping gene). Immunohistochemistry with anti-HD-5 and histological Paneth cell staining were performed in 10 patients with NOD2 mutations or wild-type genotypes. Results: Ileal expression of HD-5 and HD-6, but not sPLA2 or lysozyme, were diminished in affected ileum, and the decrease was significantly more pronounced in patients with NOD2 mutations. In the colon, HD-5, HD-6, and sPLA2 were increased during inflammation in wild-type but not in NOD2 mutated patients. In both the colon and ileum, proinflammatory cytokines and lysozyme were unaffected by NOD2 status. Immunohistochemistry identified Paneth cells as the sole source of HD-5. Conclusion: As alpha defensins are important in the mucosal antibacterial barrier, their diminished expression may explain, in part, the bacterial induced mucosal inflammation and ileal involvement of Crohn's disease, especially in the case of NOD2 mutations.